The Prophet Muhammad’s ‘Adalah: A Catholicon For Injustice In Nigeria - Shaykh Ahmad , Yahya; Miqdad Ali, Ali (Al-Basirah Journal, 2023)
Injustice is a serious problem militating against good governance in any given society where it prevails. It contributes in no small way, to the failure recorded in political system. Itpermeate the social, economic, political and judicial aspects. Thus, it would yield negative impacts in the life of the populace. However, the indirect resistance of the modern society against it is not alien to Muslims. This is because one of the duties of the Prophets was to neutralize the corrupt practices that prevailed in their various localities. It is against this background that this paper intends to unveil the concept of justice as taught by Prophet Muhammad (SAW) as a catholicon for injustice in Nigeria. Through the use of historical and analytical methods, this paper provides a locus for understanding the theory of justice as exemplified both in theory and practice by the Prophet. The paper reveals that the Prophet did not only preach justice but also manifested it throughout his life. The paper concludes that, unless Nigeria adheres to the teachings of the Prophet who was a watershed in human history, it will be difficult, if not impossible, to put things in order.